The optimization of Gebe Airport project using PERT and CPM method - Nanang Nahendra; Iwan Nauli Daulay; Anggia Paramitha (Operations Management and Information System Studies, 2022)
Project management implementation require some methods, it is done to control the project performance. The purpose of this study is to determine the form of network planning, critical path and probability level on PT. Ghinan Indo Mandiri, Ternate City. This research doing by quantitative descriptive. The data type used is quantitative data sourced from interview and company's documents. This research uses Program Evaluation and Review Technique (PERT) and Critical Path Method (CPM). Network planning is used to find the critical paths and calculate the probability level. By using the PERT and CPM methods, the initial plan of 34 weeks for the Gebe airport project had a probability level of 97.9%. Furthermore, the crashing program accelerate 2 weeks processing time can be optimized to be 32 weeks while holding 97.9% of probability level with additional costs.